Meningkatkan Kemampuan Kognitif Peserta Didik Kelas X IPS 2 Dalam Materi Perilaku Ekonomi Melalui Pendekatan Saintifik Di Sekolah Menengah Atas Negeri 12 Kota Jambi - Rayuna; journal journal (Jurnal Pendidikan Islam, 2019)
Abstract:The purpose of this study is to improve students’ knowledgeability in economic subject in topic the economic behavioral role ineconomic activities through scientific approach for students in XIPS2 class of the state of senior high school 12 Jambi city. This studyemployed the action class research. The data collected throughobservation, documentation and interview. Furthermore, the dataanalyzed by using triangulation data. This study run from Septemberto December 2018. The result of study shows that the student’sknowledge ability increased 54.83 %, from 22.58% to 77.41%,followed by teacher’s performance from 76.66% to 90% andstudents’ activity from 41.85% to 90,25%. The results inform thatthe saintific approach can use for teachers to improve student’sknowledge ability by following the stage of sacientific approachprinciples.